What is the value of a driver licence? A contingent valuation study of Australian adults. (February 2018) - Angell, Blake; Cullen, Patricia; Laba, Tracey; Lung, Tom; Shanahan, Marian; Sakashita, Chika; Eades, Sandra; Ivers, Rebecca; Jan, Stephen
Abstract: Background: Holding a driver licence is a vital part of life for many Australians, facilitating social connections and enabling access to employment, education and health services. There is a lack of evidence, however, about the value the community attaches to driver licences. This study investigates the monetary value that a sample of Australian adults place on holding a driver licence and how such valuations vary on the basis of individual characteristics. Methodology: A contingent valuation study of 1054 Australian adult licence holders (with an oversampling of Indigenous Australians) was carried out to derive the sample's willingness to pay (WTP) to avoid losing their driver licence for a period of one year. Interval regression analyses were undertaken to determine the association between a range of demographic and driving-related characteristics of respondents and their WTP valuations. Results: The sample was representative of the Australian population in terms of state of residence and gender. Mean WTP based on the base model was $2290 to avoid losing a driver licence for a year (95% CI $2156–$2431). Indigenous participants had a mean WTP higher than other respondents ($2789 as opposed to $2240, p < .001). Once individual characteristics were controlled for, there was no significant difference in the WTP results between Indigenous and non-Indigenous participants. WTP was significantly higher for respondents who drove multiple times a week ($396 higher WTP, p = .012) than those who did not and who required a car for work compared to those who did not ($520 p = .002). WTP increased with higher incomes and was greatest for those earning over $120, 000 annually ($1352 higher than those earning under $40, 000 per year, p < .001). Those living in urban areas had a significantly lower WTP compared to non-urban residents ($407 lower than other respondents, p = .012) and WTP decreased with age ($14 lower per additional year of age, p = .03). Those who had incurred a licence suspension in the past 5 years had significantly higher WTP ($1686 p < .001), than those who had not, and those who had incurred a traffic fine in the past 5 years reported a higher WTP than those who had not ($358 p = .032). Conclusions: Holding a driver licence was found to be of substantial value to participants. While support for alternative methods of transport is important, these results highlight the importance of programs to support driver licensing, and those addressing known disparities in licensing status across population groups, such as those faced by Australia's Indigenous communities. Given the link between licensing and wider social and economic opportunities, such programs can potentially play a broad role in addressing social disadvantage and exclusion.